Effort-based decision making in schizotypy and its relationship with amotivation and psychosocial functioning - Chu, Ryan Sai Ting; Tong, Co Co Ho Yi; Wong, Corine Sau Man; Chang, Wing Chung; Tang, Wesley Chor Yin; Chan, Charlotte Cheuk Lok; Lui, Simon S. Y.; Hui, Lai Ming; Suen, Yi Nam; Chan, Kit Wa; Lee, Ho Ming; Chen, Eric Yu Hai (Frontiers in Psychiatry, 2023)
Suboptimal effort-based decision-making with reduced willingness to expend effort for high-probability / high-value reward is observed in schizophrenia patients and is related to diminished motivation, but is understudied in schizotypy. This study recruited 40 schizotypy individuals and 40 demographically-matched healthy controls, based on the Schizotypal Personality Questionnaire-Brief (SPQ-B) score (top and bottom 10% SPQ-B scores, respectively), from 2400 young people aged 15-24 years participating a population-based mental health survey in Hong Kong and examined effort allocation using the Effort Expenditure for Reward Task (EEfRT). Negative / amotivation symptoms and psychosocial functioning were assessed by the Brief Negative Symptom Scale (BNSS) and the Social Functioning and Occupational Assessment Scale (SOFAS), respectively. Schizotypy individuals were further categorized into high-amotivation and low-amotivation groups based on a median-split of BNSS amotivation domain score. Our results showed no main group effect (in either two or three-group comparison) on effort task performance. Three-group comparison analyses on selected EEfRT performance indices revealed that high-amotivation schizotypy individuals displayed significantly less increase in effortful options from low-value to high-value reward (reward-difference score) and from low-probability / low-value to high-probability / high-value reward (probability/reward difference score) than low-amotivation individuals and controls. Correlation analyses demonstrated trend-wise significance between BNSS amotivation domain score and several EEfRT performance indices in schizotypy group. Schizotypy individuals with poorer psychosocial functioning tended to exhibit smaller probability/reward difference score relative to other two groups. Overall, our findings indicate subtle effort allocation abnormalities in schizotypy individuals with high levels of diminished motivation, and suggest the link between laboratory-based effort-cost measures and real-world functional outcome.